An overview study on the TL and OSL dosimetry patent processes over time - P. B. R. Gasparian; A. L. M. C. Malthez; L. Mariano; L. L. Campos; R. Politano (Brazilian Journal of Radiation Sciences, 2023)
Since its discovery, ionizing radiation has been used in many different applications. Materials and methods have been developed to measure and quantify radiation doses.  Thermoluminescence (TL) and Optically Stimulated Luminescence (OSL) are two techniques used for radiation dosimetry. Both TL and OSL are primarily applied in several areas, such as dating of ancient materials, equipment quality control and individual monitoring. One of the parameters to measure the knowledge and development of a technology is the number of patents related to the field. In this work, we established a methodology for patent search on the World Intellectual Property Organization (WIPO) database aiming to review the development of TL and OSL dosimetry over time. We concluded that along with the OSL technique development, the TL technique should continue to be explored in radiation dosimetry.